IMPLEMENTASI DANA DESA DALAM PENGUKURAN KINERJA PROGRAM PEMBANGUNAN DESA TASIK RAYA: ANALISIS BALANCED SCORECARD DAN PENGEMBANGAN KAPASITAS APARATUR DESA - Andriyanto Andriyanto; SM. Guntur; Sri Hidayanti (Indragiri Research Center (ingreat), 2026)
This study aims to describe and analyze the implementation of the Village Fund (Dana Desa) in measuring the performance of development programs in Tasik Raya Village using the Balanced Scorecard approach, as well as to examine the role of village apparatus capacity development in supporting program effectiveness. This research employs a qualitative approach with data collection techniques through interviews, observation, and documentation. Informants were selected using purposive sampling, consisting of village officials and community beneficiaries. Data analysis was conducted using the Miles and Huberman model with the Balanced Scorecard approach, which includes financial, community, internal process, and learning and growth perspectives. The results show that the implementation of the Village Fund has been relatively effective, particularly in financial accountability and community benefits; however, several challenges remain, including limited community participation, suboptimal coordination in program implementation, and insufficient development of village apparatus capacity. Therefore, strengthening the capacity of village apparatus is an important factor in improving the effectiveness of Village Fund implementation and achieving more optimal and sustainable village development performance.